Compressive Strength, Shrinkage Rate and Temperature Profile of Concrete Containing Varying Percentage of Fine Metakaolin - Kamal, Mohd Amirul Hisham; Abd Majid, Masni; Mohd Hanif Ismail, (Recent Trends in Civil Engineering and Built Environment, 2024)
Supplementary cementitious materials (SCM) have shown to be a crucial component of concrete with exceptional strength and performance. One of the SCM materials, metakaolin (MK), is produced by calcining kaolinite. widely used as a pozzolanic ingredient in concrete to improve the strength and durability. The usage of ordinary Portland cement had result in increasing the negative affect due to its properties. This study is to investigate the concrete compressive strength by using fine metakaolin (FMK) in various ratios to partially replace cement in concrete mixture. For replacement fine metakaolin, different percentages were used which is 0%, 10%, and 15%. This mixture will be cast in two different types of moulds: a cube mould measuring 100mm x 100mm x 100mm and a prism mould measuring 100mm(W) x 100mm(H) x 300mm(L). The strength is measured after 7days, 28 days, and 56 days of curing. The concrete compressive test indicates that increasing in usage of FMK can increase the concrete compressive strength than ordinary concrete mixture. Optimum replacement of FMK for cement was 15% which increase the physical quality of concrete.